Assessing the Rooftop Rainwater Harvesting Potential in Urban Residential Areas of Pakistan: A Case Study of Model Town, Lahore, Pakistan - Siddiqui, Romana; Siddiqui, Saima (International Journal of Economic and Environmental Geology, 2018)
Rainwater harvesting (RWH) is widely recognized as an alternative water resource for domestic water supply in different parts of the world, mainly due to water scarcity. Availability of potable water is the major issue in Pakistan due to increase in population density and decrease in permeable surfaces. In this scenario, rainwater can be used as a reliable substitute of fresh water resource. In this study RWH potential in Model Town Lahore is computed for rooftops of buildings by using ArcMap 10.4.1. The RWH model is also proposed at household level with its utilities. Currently, Lahore is going through the phase of rapid population growth; unchecked immigration and reckless urban sprawl followed by undue extraction of groundwater. The water table of Lahore is depleting with an average rate of 55cm (0.55m) per annum, while the recharging water resources of Lahore aquifer are diminishing. With an average annual rainfall i.e. 628.6 millimeters (244.8 inches), Lahore is suitable for rainwater harvesting (RWH). The total estimated rainwater harvesting (RWH) potential of rooftops in Model Town Lahore is 535,756 cubic meters (535,756,000 liters) per year. The methods used in this study prove to be an effective tool for preliminarily estimation of the regional rainwater harvesting potential. RWH is an economic, environmental friendly and easy to install system. It is concluded that RWH is the best functional technique to avert the present and future water crisis in Pakistan.